LEGAL CERTAINTY IN EXPRESSING OPINIONS IN PUBLIC DURING THE INDUSTRIAL REVOLUTION ERA ACCORDING TO POSITIVE LAW IN INDONESIA AND SIYASAH DUSTURIYAH - Bambang Nurdiansyah; Sulastri Caniago; Wardatun Nabilah (UIN Mahmud Yunus Batusangkar, 2024)
This research aims to identify and explain the forms of restrictions on freedom of expression on social media and the forms of legal certainty regarding freedom of expression according to positive law and siyasah dusturiyah. In recent years, there have been efforts to narrow the space for expressing opinions, especially through social media. Often, people who express their opinions on social media receive unfavorable treatment after expressing their views. The type of research in this thesis is normative legal research with a statute approach and case approach. The primary data sources in this research are the Quran and Sunnah, as well as laws related to the right to freedom of expression in Indonesia. The data collection technique used in this research involves library research by searching for books, articles, journals, and websites. The data analysis technique in this research is descriptive. The research results show that, first, the forms of restrictions on freedom of expression on social media can be categorized into two forms: indirect and direct. Indirectly, through ambiguous articles in the Electronic Information and Transactions Law (UU ITE) and articles related to insulting the president and the government. Directly, through digital attacks, persecution, terror and intimidation, and criminal reporting or criminalization. Second, the forms of legal certainty in positive law were found to be in three forms: legal certainty guarantees through individual or group rights, legal certainty guarantees through the government's obligation to protect individuals who use their right to freedom of expression, and legal certainty in the form of sanctions against those who attempt to hinder others' freedom of expression. Third, from the perspective of siyasah dusturiyah, there is also legal certainty for freedom of expression through the right to express opinions and the obligation of rulers to protect those who express their views. Based on the research results, it was found that restrictions on freedom of expression have occurred, which will ultimately lead to authoritarian governance. This occurs due to the suboptimal performance of the government, making it averse to criticism and resorting to restricting freedom of expression.However, it prohibits excessive and wasteful consumption patterns, categorized as al-israf behavior.